PENGARUH SPIRITUALITAS TERHADAP ETOS KERJA PRESPEKTIF AL QURAN - Subhan Subhan (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2018)
Abstract Physical and instinctive needs are natural and neutral, can not in itself be said that one's needs are higher than the other. It is precisely the way in which people manage and satisfy those needs that can be given a praiseworthy or despicable title. In the view of Islam, if these needs are met with the actions carried out according to Islamic guidance, then it will be a commendable act. Conversely, if these needs are met with acts that violate the guidance of Islam then he becomes a disgraceful act. Spiritual intelligence associated with the problem of meaning, value, spiritual intelligence is able to guide humans to find meaning and can also guide people in reaching his ideals. Spiritual intelligence goes beyond the ability to intelligently think, feel, act and behave in situational contexts or given frameworks. Spiritual intelligence enables humans to be wise in reflecting on the situation to find themselves more meaningful so as to be able to transform something more precious. With the formation of spirituality culture in the workplace, it is expected to form employees who are happy, know and able to meet the purpose of life. Such employees generally have a balanced life between work and person, between duty and service. In general, they also have higher performance. The results of a large consulting firm, the application of a spiritual work environment increase productivity and reduce turn over. Other studies show that employees of high spiritual intelligence and supported by a work environment that is also spiritual, positively become more creative, have high job satisfaction, are able to work well in teams, and have a high commitment to the organization. Keywords : Guidance of Islam, Spirituality